A Sociological Exploration of Institutional, Sociocultural, and Economic Barriers to Women's Higher Education Aspirations in Balochistan - Bushra Manzoor; Dr. Hamadullah Kakepoto; Dr. Ahmed Ali Brohi (Indus Journal of Social Sciences, 2025)
A developing approach to economic and social empowerment is higher education. It enables people to acquire the knowledge and abilities they need to pursue their career goals and make significant contributions to society. The socio-cultural, economic, and institutional constraints pose a large number of issues for female students in Balochistan. This study adopted a qualitative research methodology by using purposive sampling to gather information from 73 female students and female teaching faculty across three major universities in Quetta. Data was collected through in-depth interviews and FGDs, which were then analyzed thematically. The study contextualizes the findings in broader social contexts through the application of Bronfenbrenner's Ecological Systems Theory and Connell's Framework of Gender Relations. Five core themes were comprising sociocultural barriers, economic limitations, institutional deficiencies, academic pressures, and opportunities for empowerment, were discussed. Findings from the study suggest the issue of continued patriarchal thought domination, weak institutional setup, and economic hardship in the region; besides them, alternatives like women's universities, scholarships, and mentoring are highlighted. Proposed reform includes gender-inclusive reform, financial help, and community involvement toward making a conducive higher education environment all around Balochistan, that would turn out to be women-friendly, gender-equitable, and woman-inclusive.